Evaluation the effect of different instrumentation and obturation techniques on apical microleakage . (In vitro comparative study) (Mustansiria Dental Journal, 2018)
This in vitro study evaluated and compared the apical sealing ability of twoobturation techniques and two type of instrumentation. A total of 120 teeth werecollected randomly divided into two groups 60 roots prepared using hand protaper,other 60 roots prepared using rotary protaper .Each group was subdivided randomlyinto two obturation groups of 30 roots for each; in group A- obtura II was used ,andin group B-thermafill (TF) was used. Then the samples in all groups left for a week atroom temperature. After coronal sealing, all surfaces of the root covered with threelayer of nail polish except the apical 2mm, then each sample immersed in 10% blackIndian ink dye for 72 hours .After that the samples rinsed and nail polish removed.then samples cleared & decalcified.Data had been collected from independentexaminers and statistically analyzed using student t-test. The stereomicroscopicresults showed that there was highly significant difference between hand and rotaryinstrumentation, with in favor of rotary instrumentation technique. Concerning theobturation techniques, Thermafill showed best apical sealing followed by Obtura II;however, the differences were not significant.